Integrating "Super Skills for Exams" Programme in the School Curriculum to Support Adolescents Preparing for Their National Examinations in Turkey - Bilge Uzun; Asli Orman; Cecilia A. Essau (MDPI AG, 2024)
Examination stress is the most common stressor reported by adolescents across the globe. Exam stress involves mental distress related to anticipated academic challenges or fear of failure in the examinations, test anxiety, or fear of being unable to meet certain expectations of themselves or others. The aim of this study was to determine the effectiveness of a transdiagnostic resilience program (Super Skills for Exams; SSE), when integrated in the school curriculum and delivered by the school counsellors, in reducing exam stress among adolescents who are preparing for their national examinations. SSE is based on the principles of Cognitive Behaviour Therapy (CBT), behavioural activation, and social skills training, and includes sessions in promoting healthy lifestyles. Participants were 7129 (3661 female and 3468 male) adolescents in grades 7 and 8, from all the 245 secondary schools from Ugur College in seven regions and 31 cities across Turkey. All the participants completed a set of questionnaires to measure self-efficacy for learning and test anxiety, academic stress, emotion regulation, and lifestyles. Results revealed significant reduction in academic stress (i.e., test anxiety, work pressure, self-expectation, and despondency) and maladaptive emotion regulation strategies, and significant increase in self-efficacy and adaptive regulation strategies following the intervention. Adolescents who participated in SSE reported an increase in the consumption of healthy food. This study provides preliminary empirical support for the integration of SSE within the school curriculum for helping adolescents cope with exam stress as they prepare for their national exams.